Nitride Spinel: An Ultraincompressible High‐Pressure Form of BeP2N4. Issue 7 (7th November 2019) - Vogel, Sebastian; Bykov, Maxim; Bykova, Elena; Wendl, Sebastian; Kloß, Simon D.; Pakhomova, Anna; Dubrovinskaia, Natalia; Dubrovinsky, Leonid; Schnick, Wolfgang
Abstract: Owing to its outstanding elastic properties, the nitride spinel γ‐Si3 N4 is of considered interest for materials scientists and chemists. DFT calculations suggest that Si3 N4 ‐analog beryllium phosphorus nitride BeP2 N4 adopts the spinel structure at elevated pressures as well and shows outstanding elastic properties. Herein, we investigate phenakite‐type BeP2 N4 by single‐crystal synchrotron X‐ray diffraction and report the phase transition into the spinel‐type phase at 47 GPa and 1800 K in a laser‐heated diamond anvil cell. The structure of spinel‐type BeP2 N4 was refined from pressure‐dependent in situ synchrotron powder X‐ray diffraction measurements down to ambient pressure, which proves spinel‐type BeP2 N4 a quenchable and metastable phase at ambient conditions. Its isothermal bulk modulus was determined to 325(8) GPa from equation of state, which indicates that spinel‐type BeP2 N4 is an ultraincompressible material. Abstract : Nitride spinel : At 47 GPa and 1800 K phenakite‐type BeP2 N4 was transformed into the spinel‐type form of BeP2 N4 using a laser‐heated diamond anvil cell. Its crystal structure was investigated using pressure‐dependent in situ synchrotron XRD measurements and its isothermal bulk modulus was determined to >300 GPa, which renders spinel‐type BeP2 N4 an ultraincompressible material.